2006
DOI: 10.1182/blood-2006-05-021881
|View full text |Cite
|
Sign up to set email alerts
|

Induction of FcγRIIA expression in myeloid PLB cells during differentiation depends on cytosolic phospholipase A2 activity and is regulated via activation of CREB by PGE2

Abstract: FcγRIIA expressed on neutrophils and monocytes has a fundamental role in combating bacterial infections. In the present study, the requirement of cytosolic phospholipase A2 (cPLA2) for induction of FcγRIIA expression was studied in a model of cPLA2-deficient PLB-985 cells (PLB-D cells). FcγRIIA was acquired only during differentiation of PLB but not of PLB-D cells induced by either 1,25-dihydroxyvitamin D3, retinoic acid, or interferon γ. Addition of prostaglandin E2 (PGE2) to PLB-D cells undergoing differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…In our previous studies, we have shown that cPLA 2 a exerts its effect on gene expression and protein upregulation in the leukemic PLB cells (18) and in primary rat microglia (19,31) via the production of PGE 2 . To study whether PGE 2 is involved in TNFa-induced ICAM-1 upregulation in endothelial ECV-304 cells, we first studied the secretion of PGE 2 induced by TNF-a during 24 h. As shown in Fig.…”
Section: Cpla 2 a Regulates Tnf-a Induction Of Icam-1 Upregulation Inmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies, we have shown that cPLA 2 a exerts its effect on gene expression and protein upregulation in the leukemic PLB cells (18) and in primary rat microglia (19,31) via the production of PGE 2 . To study whether PGE 2 is involved in TNFa-induced ICAM-1 upregulation in endothelial ECV-304 cells, we first studied the secretion of PGE 2 induced by TNF-a during 24 h. As shown in Fig.…”
Section: Cpla 2 a Regulates Tnf-a Induction Of Icam-1 Upregulation Inmentioning
confidence: 99%
“…cDNA was amplified via PCR using Thermus aquaticus DNA polymerase under conditions found to amplify cDNA molecules in a linear fashion. For detection of the Eprostanoid (EP) receptors, we used published primers (10) that were used by us before (19). PCR amplification was performed in a microprocessor-controlled incubation system (Crocodile II; Appligene, Plessanton, CA).…”
Section: Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoblot detection of cPLA 2 and b-actin in peritoneal cell was detected as described previously [40]. Immunoblot detection of cPLA 2 , MPO and b-actin in mouse joints was performed after being frozen in liquid nitrogen, wrapped with aluminium foil and crushed before boiling in lameli buffer.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The implication of the heterotrimeric G protein Gs, which is known to be present and active in neutrophils [165,166], in the mediation of the increases of cAMP in neutrophils remains to be investigated. The role of cAMP in dampening neutrophil responses, while generally admitted, is however far from being completely understood as is the cAMPmediated regulation of gene transcription in neutrophils [167,168].…”
Section: Downstream Effector Pathwaysmentioning
confidence: 99%